2015
DOI: 10.1007/s10856-014-5350-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructured zirconia surfaces modulate osteogenic marker genes in human primary osteoblasts

Abstract: In dentistry, zirconia has been used since the early 1990s for endodontic posts, more recently for implant abutments and frameworks for fixed dental prostheses. Zirconia is biocompatible and mechanically strong enough to serve as implant material for oral implants. Although several zirconia implant systems are available, currently the scientific and clinical data for zirconia implants are not sufficient to recommend them for routine clinical use. Here the influence of microstructured yttria-stabilized zirconia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 32 publications
4
43
1
Order By: Relevance
“…Among the different surface chemical treatments already proposed in the literature for this purpose, hydrofluoric acid (HF) etching appears to be a good candidate [9][10][11][12]. Besides zirconia dental implants with acid etched surface are already commercialized (CeraRoot implants with ICE™ surface) and apparently have shown a similar success rate as compared to Titanium implants after five years of follow-up study [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different surface chemical treatments already proposed in the literature for this purpose, hydrofluoric acid (HF) etching appears to be a good candidate [9][10][11][12]. Besides zirconia dental implants with acid etched surface are already commercialized (CeraRoot implants with ICE™ surface) and apparently have shown a similar success rate as compared to Titanium implants after five years of follow-up study [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sandblasted and acid etched as well as sandblasted, acid‐etched, and thermally treated specimens showed downregulation of alkaline phosphatase and upregulation of osteocalcin after 3 days compared with machined or sandblasted surfaces, indicating a progressive osteoblast differentiation on these surfaces (Bergemann et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Ito et al showed that the combination of both treatments leads to an increase in the proliferation rate and expression of ALP activity of osteoblast-like cells (MC3T3-E1) [14] and Bergemann et al. found recently that it enhanced the human primary osteoblast maturation [15].…”
Section: Introductionmentioning
confidence: 99%